2021
DOI: 10.3389/fsufs.2021.700642
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Characterization of Cabernet Sauvignon Wines From Different Geographical Indications of Mendoza, Argentina: Effects of Plant Material and Environment

Abstract: The chemical and sensory characteristics of the wines are related to the geographical origin of the grape, as a result of the interplay between the plant material (G), its acclimatization to the environment (E) and the human factor that influences both the vineyard and the winery. The range of phenotypes that a single genotype can express depending on its environment is known as phenotypic plasticity and is the result of G × E interaction. The present study evaluated the independent and interactive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…This grapevine adapts to a wide range of environments with a board phenotypic plasticity (including differential wine sensory attributes). Then, this variety has a high capacity of acclimatization to the different environments and adaptation to climate change [29][30][31].…”
Section: World Distribution Of Main International Grape Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This grapevine adapts to a wide range of environments with a board phenotypic plasticity (including differential wine sensory attributes). Then, this variety has a high capacity of acclimatization to the different environments and adaptation to climate change [29][30][31].…”
Section: World Distribution Of Main International Grape Varietiesmentioning
confidence: 99%
“…According to several authors, it is expected that the combination of plant material (genotype), fungi and bacteria population (microbiome), soil and climate conditions, and all factors related with vineyard management and winemaking affect the quality of grapes and consequently the wines produced. Thus, interactions between all of these factors are usually mentioned as the "terroir" and are finally expressed in the grape composition and consequently in wine characteristics [31][32][33]. According to Magalhães [34], on the basis of these interactions, the concept of "terroir" has been extensively adopted for the majority of the authors.…”
Section: Impact Of Different Terroirs On Grape Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, higher altitude tends to promote cyanidin-type or non-acylated anthocyanins ( Xing et al, 2016 ; Muñoz et al, 2021 ; Urvieta et al, 2021 ). Certainly, UV-B has been pointed out to be the main contributor to this effect by direct activation of the flavonoid 3′-hydroxylase (F3′H)-mediated branch of the phenylpropanoid pathway in berry skins, which produces 3′,4′-hydroxylated flavonoids such as quercetin-type flavonols, cyanidin-type anthocyanins, catechin and epicatechin ( Berli et al, 2011 ; Martínez-Lüscher et al, 2014 ; Xing et al, 2016 ).…”
Section: Altitude and Chemical Composition Of Grapes And Winesmentioning
confidence: 99%
“…In recent years, various studies on origin in various producing areas are still as a topic of great interest ongoing, such as elemental and phenolic analysis of Italian (Veneto, Umbria, and Friuli) wines, metabolomic profiles of Spanish (Rioja and Priorat) red wines, and color and volatile analyses of Australian (Adelaide Hills, Yarra Valley, Mornington Peninsula, Northern and Southern Tasmania) wines, etc. [ 14 , 15 , 16 , 17 ]. Meanwhile, the study about wines of different grape varieties and origins, yeast strains, and spontaneous fermentation also strongly indicated that volatile chemical differences between wines were mainly driven by grape origin [ 18 ].…”
Section: Introductionmentioning
confidence: 99%